A Scoping Review and Analysis of a Series of Country Experiences to Inform the Chilean Health Financing Reform; [Revisão de Escopo E Análise de Uma Série de Experiências Nacionais Para Embasar a Reforma Do Financiamento Da Saúde No Chile]; [Revisión Exploratoria y Análisis de Diversas Experiencias de Distintos Países Para Fundamentar la Reforma del Financiamiento de la Atención de Salud en Chile] - Bachelet-Norelli, V; Osorio-Ulloa, M (Pan American Health Organization, 2025)
Objective. To analyze international health reform experiences to inform Chile’s health financing reform efforts. Methods. A scoping review methodology was used. Six countries that met inclusion criteria were used for the comparative analysis: Canada, Denmark, Estonia, France, Slovenia, and Spain. A profile was prepared for each country describing the financing system, the structures in charge of managing the public health insurance system, and the institution responsible for financing and its attributions regarding healthcare providers. Results. The search identified 188 records, from which the country profiles were created. We narratively analyze the findings, focusing on a) financing (revenue collection and pooling), b) purchaser–provider relationship and payment mechanisms, c) governance of institutional capacities and policies for reform, and d) voluntary private health insurance. For each of these dimensions, we make focused recommendations that could aid the ongoing effort on healthcare reform in Chile to move toward universal public insurance with a mixed payment mechanism for public and private providers. We also discuss the type of institutional governance required and the transition from mandatory to complementary private insurance. Conclusions. Our analysis and underlying assumptions allow us to provide recommendations for the current reform process in Chile, focusing on the advancement of universal public insurance with a mixed payment mechanism for public and private providers, the type of institutional governance to be developed to achieve it, and the transition from the current mandatory private insurance to complementary private insurance. © 2025 Pan American Health Organization. All rights reserved.